Farmer’s Lung Disease - Catur Agustiyanto; Ariani Permatasari (Jurnal Respirasi, 2021)
Occupational lung disease is a lung disease or disorder that occurs due to the inhalation of dangerous particles, mist, vapors, or gases while a person is working. The materials accumulate in the respiratory tract or lungs. The type of lung disease that occurs depends on the size and type of the inhaled material. Substances that cause occupational lung disease are toxic materials called noksa. Noksa is a substance that can cause damage to the anatomical structure of body organs and cause respiratory tract function disorders. The lung disease that many farmers experience is often called farmer's lung disease (FLD). FLD is part of hypersensitivity pneumonitis (HP). HP, also known as extrinsic allergic alveolitis, is a group of lung diseases caused by the inhalation of various antigenic organic materials. The most common cause is exposure to agricultural biological dust derived from straw, mold spores, or other dust. HP can be a secondary reaction due to repeated and prolonged inhalation of specific antigens in sensitive individuals. Diagnosis of FLD is often inaccurate. Many of these cases are diagnosed as idiopathic interstitial lung disease. A complete anamnesis should be performed, especially regarding the history of exposure to moldy hay, previous work, and domestic animals, to determine the existence of a history of exposure to the antigen and to confirm the diagnosis.